(untitled) (Research, Society and Development, 2024)
Introduction: Cesarean birth is a surgical procedure used to deliver a fetus through the abdominal route rather than vaginally. In Brazil, this procedure can be carried out by request of the pregnant woman, known as an elective cesarean. Our aim was to estimate the average cost of an elective cesarean section using the micro costing technique with the TDABC methodology. Methodology: This descriptive case study utilized the eight-step technique for the TDABC methodology. The study involved interviews, field analysis, review of medical records and cost spreadsheets, as well as the calculation of the cost capacity rate (CCR) in Excel spreadsheets. Numerical variables were analyzed using averages and categorical variables using percentages. Results and Discussion: The study determined an average cost of R1,400.51 reais per cesarean procedure. Based on the exchange rate, this cost can be estimated at 273.53 dollars or €256.03 euros. Final Consideration: The analysis allowed for comparison with previous studies and highlighted the disparity and relative cost containment in our reality. It also contributed to the pricing of packages when contracts are reviewed.